2021
DOI: 10.1002/jcp.30649
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates reactive astrogliosis and glial scar formation following cerebral ischemia and reperfusion injury mediated by GSK‐3β and RIP1K

Abstract: Even though astrocytes have been widely reported to support several brain functions, studies have emerged that they exert deleterious effects on the brain after ischemia and reperfusion (I/R) injury. The present study investigated the neuroprotective effects of melatonin on the processes of reactive astrogliosis and glial scar formation, as well as axonal regeneration after transient middle cerebral artery occlusion. Male Wistar rats were randomly divided into four groups: sham‐operated, I/R, I/R treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…Under pathophysiological conditions, most NSCs eventually differentiate into astrocytes which in the injured brain can be transformed into reactive astrocytes and promote the formation of glial scars, thereby inhibiting axon regeneration and hindering neurogenesis 13,37 . In this study, we found that the expression of miR‐199a‐5p elevated at 14th d after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 53%
“…Under pathophysiological conditions, most NSCs eventually differentiate into astrocytes which in the injured brain can be transformed into reactive astrocytes and promote the formation of glial scars, thereby inhibiting axon regeneration and hindering neurogenesis 13,37 . In this study, we found that the expression of miR‐199a‐5p elevated at 14th d after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 53%
“…Chen et al reported that administration with melatonin attenuated TRIF expression, an adapter molecule of TLRs, and ultimately prevented the conversion of astrocytes from anti-inflammatory (A2) to pro-inflammatory (A1) phenotype ( Chen et al, 2020 ). In addition, in rats subjected to MCAO/R, melatonin administration could effectively decrease glial fibrillary acid protein (GFAP) expression, C3, and S100A10, suggesting that melatonin inhibited reactive astrogliosis and A1 astrocyte polarization ( Yawoot et al, 2022 ). Besides, melatonin was also shown to reduce astrocyte-mediated inflammatory response by inhibiting glycogen synthase kinase-3 beta (GSK-3β) expression levels and receptor-interacting serine/threonine-protein 1 kinase (RIP1K) activities, consequently enhanced axonal regeneration and promoted neurobehavioral recovery ( Yawoot et al, 2022 ).…”
Section: The Mechanism Of Melatonin’s Neuroprotective Effect In Cereb...mentioning
confidence: 99%
“…In addition, in rats subjected to MCAO/R, melatonin administration could effectively decrease glial fibrillary acid protein (GFAP) expression, C3, and S100A10, suggesting that melatonin inhibited reactive astrogliosis and A1 astrocyte polarization ( Yawoot et al, 2022 ). Besides, melatonin was also shown to reduce astrocyte-mediated inflammatory response by inhibiting glycogen synthase kinase-3 beta (GSK-3β) expression levels and receptor-interacting serine/threonine-protein 1 kinase (RIP1K) activities, consequently enhanced axonal regeneration and promoted neurobehavioral recovery ( Yawoot et al, 2022 ). Mechanistically, suppression of GSK-3β can reduce NF-κB nuclear translocation and upregulate cyclic AMP response element-binding protein (CREB) transcription.…”
Section: The Mechanism Of Melatonin’s Neuroprotective Effect In Cereb...mentioning
confidence: 99%
“…Additionally, astrocytes in this region display elongated and polarized processes with an increased GFAP expression and expression of factors involved in extracellular matrix remodeling and clustering of reactive astrocytes [410]. After ischemia and reperfusion injury, melatonin has been shown to attenuate reactive astrogliosis and glial scar formation, reduce the infarct volume, and, consequently, enhance axonal regeneration and promote neurobehavioral recovery in adult rats [411,412]. These effects of melatonin are related to a reduction in the activity of glycogen synthase kinase-3 beta (GSK-3β) and receptor-interacting serine/threonine-protein 1 kinase (RIP1K), proteins involved in astrocyte responses, after the treatment [412].…”
Section: Melatonin In Astrocyte Activationmentioning
confidence: 99%
“…After ischemia and reperfusion injury, melatonin has been shown to attenuate reactive astrogliosis and glial scar formation, reduce the infarct volume, and, consequently, enhance axonal regeneration and promote neurobehavioral recovery in adult rats [411,412]. These effects of melatonin are related to a reduction in the activity of glycogen synthase kinase-3 beta (GSK-3β) and receptor-interacting serine/threonine-protein 1 kinase (RIP1K), proteins involved in astrocyte responses, after the treatment [412]. Furthermore, melatonin pretreatment has been shown to reduce the increased expression of Nox2 and Nox4 in astrocyte neurons and endothelial cells, reduce RONS levels, and inhibit cell apoptosis [413].…”
Section: Melatonin In Astrocyte Activationmentioning
confidence: 99%